Rancang Bangun Miniatur Kapal Bentuk V Bottom sebagai Simulator Inclining Test - Sirait, Egbert Josua; Purnawanti, Yani Nurita (Jurnal Pengelolaan Laboratorium Pendidikan, 2024)
Literature studies on the application of the inclining test, in accordance with BKI (Indonesian Classification Bureau) standards, have been widely applied to large ships. But in practice in the field, large ship media is difficult to obtain. In supporting ship building practicum and ship stability, especially in inclining test practicum, a miniature ship is really needed to help students understand ship building, ship stability, and understand the inclining test procedure which is a benchmark for ship stability. So in this study, focusing on ship design, for fabrication of ship buildings and the addition of lubricating media, as well as calculation tables as a guide in carrying out building practicum and ship stability. In the fabrication of miniatures that have been produced, the stability point values are KG = 3.54 cm, KM = 20.17 cm, KB = 3.41 cm, GM = 16.63 cm, and BM = 16.73 cm where the results are has been obtained in accordance with the theory of stability where the position of each point is in accordance with the top order of K, G. B. and M.